A Barrel of Oil or a Bottle of Wine : How Do Global Growth Dynamics Affect Commodity Prices? - Saadi Sedik, Tahsin; Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2011)
This paper investigates the causes of extreme fluctuations in commodity prices from 1990 to 2010. Analyzing two very distinct commodities-crude oil and fine wine, we find that macroeconomic factors are the main determinants of commodity prices. Although supply constraints have the expected effect, aggregate demand growth is the key factor. The empirical results show that while advanced economies account for more than half of global consumption, emerging economies make up the bulk of the incremental change in demand, thereby having a greater weight in commodity price formation. The results also show that the shift in the composition of aggregate commodity demand is a recent phenomenon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet